Improving the Digital Skills of Young Voters Through Education to Prevent Election Hoaxes Using the Kalimasada Mafindo Application - Gushevinalti, Gushevinalti; Sakinah, Nazwa Iqrami; Ridiansyah, Oka (CV Media Inti Teknologi, 2024)
The practical training on fact-checking using Kalimasada Mafindo was conducted to improve digital literacy and participants' ability to counteract the spread of hoaxes about elections. This training was held on 2 July 2024 at the Village Hall Hall, attended by young voters and village officials in Panca Mukti Village who were enthusiastic about understanding the importance of information verification in the digital era. The resource person or facilitator of this activity is Mafindo Volunteers, who are certified in the Fact Check. The training material includes an introduction to Kalimasada as one of the tools in the fact-checking process, techniques for identifying false information, and steps to verify data through credible sources. The participants showed positive and interactive responses during a practice session with the Kalimasada chatbot with the WhatApps 085921600500 number, where they successfully used Kalimasada to verify the correctness of information quickly and accurately. The final evaluation showed that participants understood the concept of fact-checking and had adequate ability to apply it in daily life to combat disinformation, significantly ahead of the 2024 Pilkada.